2021
DOI: 10.1002/jnm.2938
|View full text |Cite
|
Sign up to set email alerts
|

Simple two‐stage weighting factor design for finite control set model predictive control of modular multilevel converters

Abstract: Due to discrete nature of power converters, finite control set model predictive control (FCS‐MPC) is considered as an attractive choice for these systems. Since this control technique provides advantages like improved dynamic performance and inclusion of several control objectives in a single cost function, it is especially appropriate for topologies like modular multilevel converters (MMCs), where multiple control goals, that is, output and circulating currents control, and cells' capacitor voltage balancing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The mathematical and logical treatment of the latter can be accomplished within the framework of discrete time S. The model of the MLI is contingent upon the input DC-link voltage, capacitor voltages, and switching states. Once the prediction model is determined, it can be incorporated as the cost function [23]. The incorporation of weighting elements is crucial in the formulation of the cost function.…”
Section: Model Predictive Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…The mathematical and logical treatment of the latter can be accomplished within the framework of discrete time S. The model of the MLI is contingent upon the input DC-link voltage, capacitor voltages, and switching states. Once the prediction model is determined, it can be incorporated as the cost function [23]. The incorporation of weighting elements is crucial in the formulation of the cost function.…”
Section: Model Predictive Controlmentioning
confidence: 99%
“…Among its variants, Finite Control Set Model Predictive Control (FCS-MPC) has garnered significant attention for controlling MLIs with superior performance, robustness, and accuracy. This approach enables the inverter to predict future behavior based on a discrete set of control signals and enables a precise modulation and high-speed response to system dynamics [18][19][20][21][22][23][24]. In the renewable energy sector, integrating FCS-MPC with MLIs holds significant potential to boost energy conversion efficiency, grid integration, and overall system reliability.…”
Section: Introductionmentioning
confidence: 99%
“…Unstable systems are considered as another challenging dynamic system that is first stabilized via an inner loop of the proposed method, and afterward, the other control objectives, reference tracking, and disturbance rejection are obtained by the outer control loop. Another critical issue in all of model predictive methods is weighting factor adjustment due to their direct effect on results (Rossiter and Aftab, 2021; Dragievi and Novak 2019; Khosravi et al, 2021). In many studies, it is shown that the PFC can be combined well with fuzzy control techniques to deal with nonlinear uncertain systems (Chang and Yang, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, they also suffer from higher computational burden and tend to increase the complexity of the controller. Miscellaneous methods such as twostage weighting factor tuning technique 67 and equal-weighted weighting factor selection technique 68 also tend to increase the computational cost of the control algorithms and are not feasible for practical implementation 47,[69][70][71][72][73] . In comparison the these methods, some of the MCDM methods do not pose computational challenges and are ideally aligned for implementation on the modern hardware 39,74,75 .…”
mentioning
confidence: 99%